2008
DOI: 10.1016/j.mcn.2008.06.011
|View full text |Cite
|
Sign up to set email alerts
|

Dopamine transporter endocytic determinants: Carboxy terminal residues critical for basal and PKC-stimulated internalization

Abstract: Dopamine (DA) reuptake terminates dopaminergic neurotransmission and is mediated by DA transporters (DATs). Acute protein kinase C (PKC) activation accelerates DAT internalization rates, thereby reducing DAT surface expression. Basal DAT endocytosis and PKC-stimulated DAT functional downregulation rely on residues within the 587-596 region, although whether PKCinduced DAT downregulation reflects transporter endocytosis mechanisms linked to those controlling basal endocytosis rates is unknown. Here, we define r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
75
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(76 citation statements)
references
References 41 publications
1
75
0
Order By: Relevance
“…Similarly, the mutation of Lys 590 and Asp 600 impaired hDAT cell surface expression due to its retention in the ER, and the G585A substitution completely blocked hDAT export from the ER (50). Finally, the central motif FREKLAYAIA (residues 587-596) in hDAT has been suggested to be essential for the constitutive internalization of the transporter (22,(42)(43). Thus, in all of these studies the potential involvement of the initial residues of DAT-CT in trafficking mechanisms was not described nor hypothesized.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, the mutation of Lys 590 and Asp 600 impaired hDAT cell surface expression due to its retention in the ER, and the G585A substitution completely blocked hDAT export from the ER (50). Finally, the central motif FREKLAYAIA (residues 587-596) in hDAT has been suggested to be essential for the constitutive internalization of the transporter (22,(42)(43). Thus, in all of these studies the potential involvement of the initial residues of DAT-CT in trafficking mechanisms was not described nor hypothesized.…”
Section: Discussionmentioning
confidence: 99%
“…DAT-Ctr9 complex formation appears to be dependent only interaction with the first 24 amino acids of DAT-CT (Tyr 574 -Glu 597 ). Interestingly, this first half of DAT-CT contains a motif (FREKLAYAIA) that was determined to be essential for constitutive DAT-mediated and PKC-stimulated internalization processes (22,42,43). The disruption of this motif in the ⌬32-CT mutant suppressed this interaction.…”
Section: Identification Of Ctr9 As a Dat-interacting Protein-mentioning
confidence: 99%
“…Further studies showed that Ala substitutions of residues 587 to 590 were sufficient to abolish PKC-mediated DAT downregulation and constitutive DAT internalization. On the basis of these results, it was suggested that the stretch of four residues is part of an endocytic braking mechanism that is relieved upon PKC stimulation (Boudanova et al, 2008). The role of this C-terminal motif in ubiquitination of the N terminus in PKC-mediated DAT endocytosis has not been elucidated and awaits further investigations.…”
Section: Regulated Traffickingmentioning
confidence: 99%
“…Studies from our laboratory (23) and others (24) indicate that a unique negative regulatory mechanism, or "endocytic brake," stabilizes DAT surface expression. PKC activation releases the endocytic brake, accelerates DAT internalization, and thereby reduces DAT surface levels and function.…”
mentioning
confidence: 91%